1976
DOI: 10.1017/s0031182000043158
|View full text |Cite
|
Sign up to set email alerts
|

The tylenchid (Nematoda) egg shell: structure, composition and permeability

Abstract: The fine structure of egg shells of four different genera belonging to the order Tylenchida has been examined. The species examined were Meloidogyne javanica, Rotylenchulus reniformis, Tylenchulus semipenetrans and Pratylenchus minyus. They are all similar in their basic structure, being composed of vitelline membrane, chitin and lipid layers, but there is considerable variability in the thickness of these layers.We have retained the conventional nomenclature because of its convenience, but it is clear that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(41 citation statements)
references
References 10 publications
0
41
0
Order By: Relevance
“…It was found that nematodes from the orders Trichinellida and Rhabditida (infraorders Tylenchomorpha, Rhabditomorpha and some of Ascaridomorpha) are characterized by endogenous three-layered egg-shell structure (Waller, 1971;Bird & McClure, 1976;Solomon & Grigonis, 1976;Wharton & Jenkins, 1978;Wharton, 1979e). Meanwhile, the Ascaridomorpha species of Ascaris Linnaeus, 1758 and Heterakis Dujardin, 1845 possess additional exogenous uterine layer (Foor, 1967;Lee & Lešťan, 1971).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was found that nematodes from the orders Trichinellida and Rhabditida (infraorders Tylenchomorpha, Rhabditomorpha and some of Ascaridomorpha) are characterized by endogenous three-layered egg-shell structure (Waller, 1971;Bird & McClure, 1976;Solomon & Grigonis, 1976;Wharton & Jenkins, 1978;Wharton, 1979e). Meanwhile, the Ascaridomorpha species of Ascaris Linnaeus, 1758 and Heterakis Dujardin, 1845 possess additional exogenous uterine layer (Foor, 1967;Lee & Lešťan, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations: LL -lipid layer; ChL -chitinous layer; VL -vitelline layer; IUL -internal uterine layer; EUL -external uterine layer Trichinellida) the lipid layer is much thicker and occupies up to quarter of total egg-shell thickness (Foor, 1967;Lee & Lešťan, 1971;Solomon & Grigonis, 1976;Wharton & Jenkins, 1978;Wharton, 1979e). The lipid layer in plantparasitic nematodes of the infraorder Tylenchomorpha was found thickening at the shell poles and having a series of lipoprotein membranes associated with it (Bird & McClure, 1976). The chitinous layer is often the thickest layer of the eggshell.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The root-knot nematodes cause measurable changes in the morphology and physiology of the host plants (Williamson and Gleason, 2003). Bird and McClure (1976), in their chemical analysis of the hydrolysis products of the egg shells of M. javanica, Rotylenchulus reinformis, Pratylenchus minyus and Tylenchulus semipenetrans have revealed a high proline content (up to 25 %) which is apparently a characteristic of nematode egg shells. Nasar et al (1980) analysed the effect of root-knot nematodes on the amino acid concentration of almond and peach root stalks and reported that the combined amino acid content of roots and leaves of bitter almond and Nemagaurd peach plants were the same in control and infested plants.…”
Section: Introductionmentioning
confidence: 99%